Effect of FYM and its Combination with Fertilizers on Growth, Biomass Production and Quality of Dalbergia sissoo Roxb. Seedlings - Raman, K.R.; Sharma, M.S.; Sivaji, V.; Mahato, G.P. (Indian Journal of Agroforestry, 2020)
A nursery trial was conducted at Forestry Faculty Campus Nursery of Birsa Agricultural University, Ranchi during rainy season of the year 2002 to study the effect of FYM and its combination with NPK on the growth, biomass production and quality of sissoo (Dalbergia sissoo Roxb.) seedlings. The seedlings had their best reflection in terms of time taken for completion of germination (11.66 days) and Dickson quality index (0.08) in the treatment getting FYM alone as external source of nutrition (T2). Maximum germination (94%) was recorded in this treatment (T2), but this treatment had statistical parity with control (T1). Root length, shoot length, root shoot ratio, collar diameter, number of leaflets per seedling, shoot fresh weight and all the three types of dry weights of seedlings recorded in the treatments getting external nutrition (FYM alone - T2, FYM along with 50 mg Urea + 50 mg SSP + 25 mg MOP per 500 g soil mixture T3and FYM along with 100 mg Urea + 100 mg SSP + 50 mg MOP per 500 g soil mixture T4) were at par among themselves but significantly superior to control (T1).